Comparative pattern of reproductive potential of Indian major carp, Cirrhinus mrigala (Cypriniformes: Cyprinidae) in the Ganges basin, India - Dwivedi, Arvind Kumar; Sarkar, Uttam Kumar; Mir, Javaid Iqbal; Tamot, Praveen; Vyas, Vipin (Journal of the Inland Fisheries Society of India, 2020)
A total of 250 samples of C. mrigala were collected to evaluate and compare gonadosomatic index, size at first maturity and fecundity from six riversof the Ganges basin. Minimum GSI was recorded for river Ken in male and female both while maximum GSI was recorded in river Ganga and river Sharda in male and female respectively. The length at first maturity (L50)in male ranged from 46.0 cm in river Sharda to 52.0 cm in river Ganga and Ghaghra. In female, L50 was lowest in river Gomti and highest in river Ken and Ghaghra. Lowest absolute fecundity was recorded from river Kenand highest for river Ganga. No significant differences were noticed (p>0.05) in absolute and relative fecundity between the rivers. Linear relationship and positive correlation (r2 =0.97-0.99) was noticed between absolute fecundity and total length (TL), total weight (TW) and ovary weight (OW) in all the populations. This study will provide new baseline information for fisheries biologists about the current stock structure of this fish across the river Ganga basin.Keywords Cirrhinus mrigala, gonadosomatic index, fecundity, wild populations, Ganga basin, India.